Sonographic stress measurement of glenohumeral joint laxity in collegiate swimmers and age-matched controls - Borsa, P. A.; Scibek, J. S.; Jacobson, J. A.; Meister, K. (The American Journal of Sports Medicine, 2005)
Background: Glenohumeral laxity that is greater than normal has been implicated as a causal factor in the development of shoulder pain and dysfunction in elite swimmers; however, quantitative evidence demonstrating greater-than-normal glenohumeral joint laxity in swimmers is lacking.